WORK ACCIDENTS RISKS ASSESSMENT AND ANALYSIS MODEL FOR A TEXTILE ENTERPRISE - Gonzales B., Carol (2004)
This work proposes a Risks Assessment and Analysis Model in a knitted fabric textile enterprise, out of the information compiled in the various working positions, with the purpose of presenting a quantified matrix of all existing risks, including its financial advantages, leading to the Head Management's decision-taking about security investment, and to improve working conditions within the enterprise.